Melukis Keluk Keseimbangan Firma Pasaran Persaingan Sempurna Untuk Tiga Jenis Keuntungan Pasaran Persaingan Sempurna Dengan Konsep ‘Potong Pizza’ - Md Yusuf, Che Rusidah (Selangor Humaniora Review, 2019)
The study was conducted on Sixth Form students taking the subject on Microeconomics. The selected title was Perfect Competition Market, which is how to draw and use curve sketches in describing the determination of short-term balance output for a more profit-generating firm, a normal profit and loss. Students found it difficult to understand concepts of economics and to draw curves as they have to draw many curves in Microeconomics. Thus, the objective of this study was to enable students to draw perfect curves for the three types of profits made by firms in the perfect competition market and to describe the curves according to the concept of a 'cut pizza'. This study involved 18 students. Data was collected through document analysis and observation. The results of this study show that students can draw and describe the curves well for three types of profit balance made by firms. To evaluate the effectiveness and validity of the study, 3 steps were taken namely pre-test, in which all students were asked to draw curves spontaneously on papers based on their memory without referring to their notes or text. Then the researcher introduced the concept of 'cut pizza' to assist students to draw curves correctly. Next, a post test on drawing curves was conducted to see how well the student understood the concept. Lastly, students were given a questionnaire to help the researcher identify the advantages and disadvantages of this action research. The 3-month study proved to be a useful guide for students in producing the curves correctly and thus able to elaborate and answer essay as well as quantitative questions. The researcher hoped that this skill will in some ways contribute to students getting better results in the Malaysian Higher School Certificate examination.